UNIFICATION OF CONDITIONS OF FORMATION AND CHARGE LEAD-ACID BATTERIE - Dzenzerskyi, V. O.; Burylov, S. V.; Buriak, O. O.; Skosar, V. Yu.; Syrenko, M. V.; Lisnychyi, V. M. (Science and Transport Progress, 2007)
The authors have developed a water cooling and gas-aerosol particles removal system during formation process or charging lead-acid batteries. The mentioned system allows increasing the output of high-quality products with identical parameters under conditions of commercial production and large-scale operation.